Koli women carrying fish basket - Mumbai Archive Project Team (Jio Institute, 2024)
The Koli community were mainly involved in fishing, though some Kolis were also cultivators. Typically, the Koli women take care of drying and selling fish, while the Koli men are engaged in fishing and distributing the day’s catch. Fish markets are dominated by Koli women, who handle the business operations.